(untitled) (Boston, 2002)
American Portraits is a two-volume collection of biographical profiles designed to supplement American History survey texts. Biography personalizes history in a unique and profound way for students, lending a sense of immediacy to the study of the past. All of the essays selected for this anthology profile the life of a given individual and explore how that person influenced and was influenced by broader historical forces. Introductions begin each part, placing the biographies in topical and chronological perspective. Supporting documents, headnotes, and discussion questions help students place the biographies in context.
Keywords: United States,Hoa Kỳ; Biography,Lịch sử